Dual GSK-3β/HDAC Inhibitors Enhance the Efficacy of Macrophages to Control Mycobacterium tuberculosis Infection - Sadaf Kalsum; Ruilan Xu; Mira Akber; Shengjie Huang; Maria Lerm; Yuqing Chen; Magda Lourda; Yang Zhou; Susanna Brighenti (Biomolecules)
Multitarget drug discovery, including host-directed therapy, is particularly promising for tuberculosis (TB) due to the resilience of Mycobacterium tuberculosis (Mtb) as well as the complexity of the host’s immune response. In this proof-of-concept study, we used high-content imaging to test a novel panel of dual glycogen synthase kinase 3 beta (GSK-3β) and histone deacetylase (HDAC) 1 and 6 inhibitor candidates for their efficacy in reducing the growth of green fluorescent protein (GFP)-expressing mycobacteria in human primary macrophages. We demonstrate that all ten test compounds, also including the GSK-3β inhibitor SB415286, exhibit an antimycobacterial effect of 20–60% at low micromolar doses and are non-toxic to host cells. Mtb growth showed a positive correlation with the respective 50% inhibitory concentration (IC50) values of GSK-3β, HDAC1, and HDAC6 in each compound, indicating that compounds with a potent IC50 value for HDAC1, in particular, corresponded to higher antimycobacterial activity. Furthermore, the results from multiparametric flow cytometry and a customized multiplex RNA array demonstrated that SB415286 and selected compounds, C02 and C06, could modulate immune polarization and inflammation in Mtb-infected macrophages involving an enhanced expression of CCL2, IL-10 and S100A9, but a decrease in inflammatory mediators including COX-2, TNF-α, and NFκB. These data suggest that GSK-3β inhibition alone can decrease the intracellular growth of mycobacteria and regulate macrophage inflammation, while dual GSK-3β/HDAC inhibitors enhance this efficacy. Accordingly, the tailored design of dual GSK-3β/HDAC inhibitors could represent an innovative approach to host-directed therapy in TB.